2017
DOI: 10.3758/s13428-017-0932-4
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling perceptual and psycholinguistic factors in syntactic processing: Tone monitoring via ERPs

Abstract: Franco, Gaillard, Cleeremans, and Destrebecqz (Behavior Research Methods, 47, 1393-1403, 2015), in a study on statistical learning employing the click-detection paradigm, conclude that more needs to be known about how this paradigm interacts with statistical learning and speech perception. Past results with this monitoring technique have pointed to an end-of-clause effect in parsing-a structural effect-but we here show that the issues are a bit more nuanced. Firstly, we report two Experiments (1a and 1b), whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 26 publications
2
14
0
Order By: Relevance
“…Recent work using the ‘click-detection’ paradigm (Lobina et al, in press) has shown that in simple sentences of the form NP-V-NP, RTs in the detection of a tone tend to decrease along the sentence. According to the authors, these results can be explained by a combination of syntactic and perceptual effects.…”
Section: General Resultsmentioning
confidence: 99%
“…Recent work using the ‘click-detection’ paradigm (Lobina et al, in press) has shown that in simple sentences of the form NP-V-NP, RTs in the detection of a tone tend to decrease along the sentence. According to the authors, these results can be explained by a combination of syntactic and perceptual effects.…”
Section: General Resultsmentioning
confidence: 99%
“…In a recent study with the tone-monitoring technique, Lobina, Demestre, and García-Albea (2018) point out that the data reported in Abrams and Bever (1969) and Bever and Hurtig (1975) may not be as robust as commonly thought, as some important factors were not considered at the time, and as a result, the experimental manipulation then used may have been confounded. Monitoring tasks, in general, exhibit a tendency of RTs to decrease across a sentence (Cutler & Norris, 1979), a factor that was not controlled for by Bever et al In fact, the tone both Abrams and Bever (1969) and Bever and Hurtig (1975) placed at the end of clauses was typically the first tone in a series, and their data clearly show a decrease in RTs from the first to the last tone position.…”
Section: Introductionmentioning
confidence: 97%
“…Monitoring tasks, in general, exhibit a tendency of RTs to decrease across a sentence (Cutler & Norris, 1979), a factor that was not controlled for by Bever et al In fact, the tone both Abrams and Bever (1969) and Bever and Hurtig (1975) placed at the end of clauses was typically the first tone in a series, and their data clearly show a decrease in RTs from the first to the last tone position. Lobina et al (2018) ran a set of experiments to reevaluate some of these results and found that the decreasing tendency is very strong in the tone-monitoring paradigm and can be in conflict with structural factors such as the wrap-up effect, which is applicable at the end of clauses and sentences. In particular, this study reports an experiment (1) in which two types of simple, monoclausal Spanish sentences with three tone positions were used, as shown below in (1), where the | symbol indicates where the tone was placed and the numbers in parentheses are the RTs, in milliseconds, to each position.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations